Mozambique : Can Information and Incentives Increase School Attendance? - World Bank (World Bank, Washington, DC, 2020)
Although more children than ever are starting school in Africa, in many countries dropout rates remain high and few students complete their schooling, especially girls. Results-based financing (RBF) has been used in many developing countries to attempt to incentivize various stakeholders such as students, parents, and teachers to achieve better results. RBF mechanisms work by linking financial incentives to measurable results, for example school attendance, dropout rates, or student test scores. Conditional cash transfers (CCTs) are one such RBF mechanism that has been used in many developing countries to incentivize individuals to take actions that they may not otherwise take, such as attending school or using preventive health services. CCTs work by giving individuals a cash transfer, conditional on verification that they have completed the prescribed behavior. CCTs have been shown to be effective in increasing school attendance in many countries, but their cost and complexity makes them difficult to manage for countries with limited administrative and budgetary capacity.